Bagaimana kanak-kanak Orang Asli gagal di sekolah? - Johari Talib,; Nazri Muslim, (Universiti Kebangsaan Malaysia, 2007)
This paper is based on a qualitative research which has been conducted in Jelebu, Negeri Sembilan in year of 2006. Research involved 90 school-age Orang Asli children of Temuan tribe who came from 60 families. Data were collected using interview technique, home visits and observations. For this purpose, researcher had organized an open-ended and structured interview to parents, teachers, children and community leaders. Research outcomes depict detail findings how Orang Asli children failed in school. The failure process started from home background, family’s socio-economic status, parental attitudes,home environment, cultural influences and in certain areas related to failure of school to implement educational policies. These whole factors seemed inter-related to one another and affect children performance in school